Crusted scabies in a renal transplant recipient treated with daily ivermectin: A case report and literature review. Issue 3 (29th March 2019) - Wang, Michael Ke; Chin‐Yee, Benjamin; Lo, Carson Ka‐Lok; Lee, Stephen; El‐Helou, Philippe; Alowami, Salem; Gangji, Azim; Ribic, Christine
Abstract: Crusted scabies is a rare disease variant associated with T‐cell dysregulation. Transplant patients are at risk of developing crusted scabies as a consequence of their immunosuppressive regimens. We report a case of crusted scabies presenting with recurrent septicemia in a 65‐year‐old renal transplant recipient, treated with daily ivermectin for 7 days after initial failure of weekly ivermectin dosing. A literature review of crusted scabies in transplant recipients consisting of 19 cases reports was summarized. Pruritus was common, and initial misdiagnosis was frequent. Most were treated with topical therapy, with one‐third receiving ivermectin. Three of seven cases presenting with a concomitant infection died. Crusted scabies is commonly misdiagnosed in transplant recipients owing to its rarity, varied appearance, and different skin distributions. It should be considered in the differential diagnosis of transplant recipients presenting with rash and pruritus, given its association with secondary infection and subsequent mortality.